Gender Equality and Outsourcing of Domestic Work, Childbearing, and Relationship Stability Among British Couples - Pia S. Schober (Journal of Family Issues, 2013)
This study investigates whether gender inequality in the division of housework and child care may be an obstacle to childbearing and relationship stability among different groups of British couples. Furthermore, it explores whether outsourcing of domestic labor ameliorates any negative effects of domestic work inequality. The empirical investigation uses event-history analysis based on 14 waves (1992-2005) of the British Household Panel Study. The author finds that the association between domestic work arrangements and family outcomes vary by the presence of children, women's employment, and gender role attitudes. Gender inequality in domestic work reduces relationship stability among egalitarian childless women and among all mothers. For first and second births as outcomes, the association is weaker and depends on the level of inequality and women's employment status, respectively. Domestic outsourcing is not significant for these family outcomes with the exception of formal child care, which is positively associated with the risk of a second birth.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich. - This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; childcare; childbearing; fathering; fertility; housework; life course; relationship breakdown